If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6v + 12 = 180 Reorder the terms: 12 + 6v = 180 Solving 12 + 6v = 180 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6v = 180 + -12 Combine like terms: 12 + -12 = 0 0 + 6v = 180 + -12 6v = 180 + -12 Combine like terms: 180 + -12 = 168 6v = 168 Divide each side by '6'. v = 28 Simplifying v = 28
| 6r+5=49 | | 2x+8+5=3x-1 | | 5z+30=180 | | .60(2-300)+0.052=.70z-205 | | 21+34=180 | | 6x(2x^2+5)-4x(3x^2+4)=z | | 10x-34=8x+20 | | 5-6[5-(9y-3)]= | | 6x+9=303 | | 2x-2=4+x-5 | | .33y+6=-12 | | 2xsq+7x+3= | | (3x+7)+(4x+5)= | | 4-secx=5 | | 28x^2y-7y= | | -10x-12=11-9x | | 3+3w=-18 | | 3.14(18)= | | 4t-5=9 | | 10+5z=100 | | 6s+3.48=35.04 | | -197-2x=73+7x | | -3-4secx=-3 | | T-9t+14=0 | | C=39.69x+0.50 | | 3.48+6s= | | t=3.48+6s | | t=6s+3.48 | | -23+7x=37+12x | | x+3x-x+8=5-x+4 | | x-0.65x=0.35x | | c=38.47+(-.25x) |